2019
DOI: 10.1186/s12864-019-5562-z
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic analysis of Leptospira interrogans serovar Paidjan and Dadas isolates from carrier dogs and comparative genomic analysis to detect genes under positive selection

Abstract: Background Leptospirosis is an emerging infectious disease worldwide that can cause high morbidity and mortality rates in humans and animals. The causative spirochetes have reservoirs in mammalian hosts, but there has been limited analysis of the genomes of isolates recovered from animals. The aims of this study were to characterize genomic features of two Leptospira interrogans strains recently isolated from asymptomatic dogs in Thailand (strains CUDO5 and CDUO8), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…In fact, some virulent genes were part of the core genome of non-pathogenic clade. This result reconfirms earlier report of virulent genes in non-pathogenic Leptospira (Kurilung et al, 2019). Various known virulence factors of Leptospira were not annotated in VFDB search analysis such as Lig proteins (Lig A, B, C) , Lipoproteins (LipL32, LipL45, LipL71) (Oliveira et al, 2011), Len proteins (Len A, B, C, D, E, F) (Stevenson et al, 2007) and Tly proteins (Tly A, B, C) (Carvalho et al, 2009) etc.…”
Section: Identification Of Clad Specific Genessupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, some virulent genes were part of the core genome of non-pathogenic clade. This result reconfirms earlier report of virulent genes in non-pathogenic Leptospira (Kurilung et al, 2019). Various known virulence factors of Leptospira were not annotated in VFDB search analysis such as Lig proteins (Lig A, B, C) , Lipoproteins (LipL32, LipL45, LipL71) (Oliveira et al, 2011), Len proteins (Len A, B, C, D, E, F) (Stevenson et al, 2007) and Tly proteins (Tly A, B, C) (Carvalho et al, 2009) etc.…”
Section: Identification Of Clad Specific Genessupporting
confidence: 93%
“…Pangenome of Leptospira contains 20822 genes which is similar to the pan-genome of other genus having diverse species such as lactobacillus (Inglin et al, 2018). Earlier study has reported pan genome on species level which are generally of 7000-8000 genes (Kurilung et al, 2019). It is obvious that a genus will have larger pan-genome than its species.…”
Section: Identification Of Clad Specific Genesmentioning
confidence: 99%
“…Our results showed considerable differences in the ecological landscape features of the distribution of each Leptospira serovar. This could be explained by the fact that different Leptospira lineages can potentially survive and adapt to different environmental conditions, as recently described by Kurilung et al (). In their study, thermal adaptation was associated with a strong positive selection for temperature in Leptospira interrogans serovars, which would be an indicator of the ability of this organism to adapt to environmental changes at serovar level.…”
Section: Discussionmentioning
confidence: 78%
“…For example, temperature and precipitation (Chadsuthi, Modchang, Lenbury, Iamsirithaworn, & Triampo, ; Desvars et al, ), high humidity and heavy rainfall (Barcellos & Sabroza, ; Goarant et al, ), as well as run‐offs, soil pH and primary productivity, have been associated with Leptospira occurrence (Fajriyah, Udiyono, & Saraswati, ; Rahayu, Sakundarno Adi, & Dian Saraswati, ; Smith, Turner, Bin, & Adam, ). In addition, a recent molecular study found strong positive selection for temperature adaptation in Leptospira interrogans at serovar level, suggesting that ecological features, such as different climatic conditions, may influence species and serovar conservation (Kurilung, Keeratipusana, Suriyaphol, Hampson, & Prapasarakul, ).…”
Section: Introductionmentioning
confidence: 99%
“…Whole genome sequencing and comparative genomic analysis of this collection will facilitate ongoing studies on identifying the putative virulent genes, pathogenic mechanisms with specific host adaptations, horizontal gene transfer mechanisms, and microbial resistance as shown in studies on the diversity and epidemiology of other microorganisms [64][65][66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%